Structural studies of human telomerase complexes by cryo-electron microscopy - Jin, Yibo (Nanyang Technological University, 2020)
Chromosomal DNA ends shorten after each round of replication due to the end-replication problem and post replication processing. The ends of linear eukaryotic chromosomes are capped and protected by protein-DNA complexes forming a structure called the telomere. The telomere length is crucial as critically short telomeres activate the DNA damage response pathway leading to cell senescence. The telomere is extended by a protein-RNA enzyme complex with reverse transcriptase function named telomerase. The process by which telomerase extends telomeres must be tightly regulated. Human telomerase is inactive in normal human somatic cells but activated by various mechanisms in 85~90% of cancer cells. Mutations in telomerase binding proteins that cause reduced telomerase activity in vivo lead to developmental disorders such as Dyskeratosis Congenita. Although many studies were carried out to study human telomerase, the molecular mechanisms behind telomerase biogenesis, recruitment and elongation process are still not fully understood. Thus, a high-resolution structure of human telomerase would provide molecular details of human telomerase catalytic cycle and recruitment. Historically, overexpression of full-length human telomerase has been shown to be difficult and does not give sufficient material for structural studies and biochemical analysis. In this thesis, I present optimised human telomerase expression and purification methods from mammalian cells, which routinely yield around 500μg of active human telomerase sample, allowing further studies of human telomerase structure by cryo-EM. The purified human telomerase sample was biochemically characterised to contain only the catalytic subunit hTERT and RNA subunit hTERC and is shown to be fully active and processive. Previously, Daniel Rhodes’ group had determined the structure of an active full-length human telomerase dimer to 25Å resolution by negative stain EM. More recently the Collins group determined the structure of monomeric human telomerase with other binding factors complex to 8Å resolution by cryo-EM. In my studies, I have obtained a 15Å structure of human telomerase dimer constituting only hTERT and hTERC by cryo-EM. In addition, HSP90/P23 bound human telomerase was purified and studied using cryo-EM. I determined a low-resolution structure of HSP90 bound human telomerase to 25Å resolution and the structure of HSP90/P23 sub-complex to 4.8Å resolution. Despite efforts spent to improve the resolution of the complex, data suggested the structural heterogeneity in the sample is the key limiting factor of the resolution of the structure, a large amount of data may compensate for the problem. Through biochemical and structural analysis, I concluded that human telomerase is likely to function as a dimer containing hTERT and hTERC alone. Finally, this thesis describes the outlook in studying human telomerase structure and its functional role at telomeres by using cryo-electron tomography (cryo-ET).